Thermodynamics, Kinetics, Morphology, and Raman studies for sH Hydrate of Methane and Cyclooctane - Gaikwad, Namrata; Kim, Hyunho; Bhattacharjee, Gaurav; Sangwai, Jitendra S; Kumar, Rajnish; Linga, Praveen (ACS Engineering Au, 2023)
Natural gas is expected to be the major energy source in the near future, and storing it in the form of gas hydrate is a safe, clean, and economical approach. However, required thermodynamic conditions and slow kinetics are the key challenges that need to address for process viability. This study involves an experimental investigation of methane and cyclooctane sH hydrate formation for possible applications in gas storage using thermodynamics, kinetics, morphology, and Raman analysis. The hydrate formation is carried out at such thermodynamic conditions where only sH hydrate would form. The four-phase (Lw-LHC-H-V) sH hydrate equilibrium is studied for the methane and cyclooctane system via dissociation along the phase boundary method which is a robust method as it delivers a greater number of equilibrium data points in a single experimental run compared to other available methods. The sH hydrate formation helps in lowering the equilibrium conditions compared with sI hydrate formation. The slow sH hydrate formation kinetics can be improved by using low tryptophan concentrations. In this work, 0.1 wt % is the optimum tryptophan concentration as the gas uptake, and the hydrate formation rate is found to be the highest compared to 0.01, 0.05, and 1 wt % tryptophan concentrations. Here, we also visually investigate the sH hydrate formation and observed that the hydrate formation occurs below the interface for the system with no tryptophan; however, hydrate formation occurrence above the interface increases with an increase in the tryptophan concentration. The increase in the hydrate formation could be dedicated to the increased gas uptake due to the increasingly porous nature of hydrate formation. The Raman analysis confirmed the presence of methane and cyclooctane in sH hydrate cages. The higher intensity of the peaks using tryptophan additionally confirms the higher hydrate formation compared to the system with no tryptophan.